“This is an age for news”: A corpus-based analysis of the word NEW(E)S in the spoken discourse of Early Modern English society (1560-1760) - Cecconi, Elisabetta (Nordic Journal of English Studies, 2017)
In my paper, I shall be examining how the voracity for news which characterises Tudor and―to a larger extent―Stuart England can be mapped on the spoken discourse of society in Early Modern England. To do so I shall analyse the Corpus of English Dialogues 1560-1760 as representative of the spoken interaction of the past in the categories of authentic and constructed dialogues. By applying tools of corpus-assisted discourse analysis (Partington 2004, 2009), I shall provide a quantitative and qualitative investigation of the word NEWS in the attempt to grasp the impact of news on people’s everyday life. While quantitative evidence will help us establish possible patterns of news vocabulary distribution from 1560 to 1760, the qualitative analysis of keywords in context will allow us to uncover collocational sets which can be interpreted in light of the evolving relationship between society and news in the historical period examined. The paper will also aim to provide an example of how corpus-assisted research in historical sociolinguistics can help us trace relations between language practices and context.